Role of Interleukin-10 (-1082A/G) gene polymorphism with the risk of ischemic stroke: a meta-analysis. (1st September 2016) - Kumar, Pradeep; Yadav, Arun Kumar; Misra, Shubham; Kumar, Amit; Chakravarty, Kamalesh; Prasad, Kameshwar
Abstract : The role of anti-inflammatory Interleukin-10 (IL-10) cytokine gene polymorphism with the risk of ischemic stroke (IS) remains controversial. The aim of present meta-analysis was to investigate the association of IL-10 (-1082 A/G) gene polymorphism with the risk of IS. A literature search for candidate gene association studies published before 29 February 2016 was conducted in the PubMed, EMBASE, Google Scholar, and TRIP database. The following search terms were used: 'Interleukin-10' or 'IL-10' and 'Ischemic stroke' or 'IS' and 'Cerebral Infarction' or 'CI' and 'genetic polymorphism' or 'single nucleotide polymorphisms' or 'SNP'. Fixed or random effects models were used to estimate the pooled odds ratios (ORs) and 95% confidence intervals (CIs). Begg's funnel plot was used to assess the potential for publication bias. In our meta-analysis, five case-control studies involving 1209 IS cases and 1139 controls were included. Overall, there was no significant association between IL-10 (-1082 A/G) [rs1800896] and risk of IS under dominant [AA + AG vs. GG], recessive [AA vs. AG + GG], and allelic [G vs.A] models. However, based on Trial of Org 10172 in Acute Stroke Treatment (TOAST) classification, we observed significant association of IL-10 (-1082 A/G) gene polymorphism with the risk of IS for Large Vessel Disease (LVD), Small Vessel Disease (SVD), and other (others due to determined and undetermined etiology) subtypes of IS. This is the first meta-analysis to conclude that IL-10-1082A/G gene polymorphism is associated with the risk of LVD, SVD, and other subtypes of IS. Further well-designed large sample size studies based on TOAST classification are needed to validate these findings.